Histone deacetylase 5 regulates the inflammatory response of macrophages. Issue 9 (8th June 2015) - Poralla, Lukas; Stroh, Thorsten; Erben, Ulrike; Sittig, Marie; Liebig, Sven; Siegmund, Britta; Glauben, Rainer
Abstract Modifying the chromatin structure and interacting with non‐histone proteins, histone deacetylases (HDAC) are involved in vital cellular processes at different levels. We here specifically investigated the direct effects of HDAC5 in macrophage activation in response to bacterial or cytokine stimuli. Using murine and human macrophage cell lines, we studied the expression profile and the immunological function of HDAC5 at transcription and protein level in over‐expression as well as RNA interference experiments. Toll‐like receptor‐mediated stimulation of murine RAW264.7 cells significantly reduced HDAC5 mRNA within 7 hrs but presented baseline levels after 24 hrs, a mechanism that was also found for Interferon‐γ treatment. If treated with lipopolysaccharide, RAW264.7 cells transfected for over‐expression only of full‐length but not of mutant HDAC5, significantly elevated secretion of tumour necrosis factor α and of the monocyte chemotactic protein‐1. These effects were accompanied by increased nuclear factor‐κB activity. Accordingly, knock down of HDAC5‐mRNA expression using specific siRNA significantly reduced the production of these cytokines in RAW264.7 or human U937 cells. Taken together, our results suggest a strong regulatory function of HDAC5 in the pro‐inflammatory response of macrophages.